Reading the Rural Queerly - Kate E. Kedley; Ryan Schey (University of Oklahoma Libraries, 2024)
In this article, we describe an interpretive framework for teachers and teacher educators to use when engaging with two areas of English language arts curriculum and research - ruralness and queerness - as they work alongside readers of young adult literature. Too often rural communities and queerness are characterized as opposed if not incompatible. This binary-i.e., urban-as-queer-affirming and rural-as-queerphobic-has become so common that queer theorists have developed the term metronormativity to name and interrogate this ideology (Halberstam, 2005; Gray, 2009; Herring, 2010). Having lived and taught in rural and small town communities, we are concerned that metronormativity can, at times, go unrecognized if not uninterrogated in educational research. By offering a framework for teaching and analyzing literature in classrooms and teacher education classrooms, we encourage readers of queer young adult literature to ask questions about how and why ideas about spaces and sexualities become naturalized ideologies that are accepted as truth. Such questions matter not only for queer youth in rural contexts. Instead, they offer productive ways to think about literature and its relationships to life for readers in urban, suburban, and other contexts regardless of their sexual identities.